Diagenesis and reservoir quality of Oligocene Barail Group of Upper Assam Shelf, Assam and Assam Arakan basin, India - Bhuyan, Deepsikha; Borgohain, Pradip; Bezbaruah, Debojit (Journal of Asian Earth Sciences: X, 2022)
•BMS and BCS units of Barail Group of rocks experienced diagenetic modification during burial history.•Lateral porosity variation is evident in the sand units within both BCS and BMS formations.•Lateral porosity is mainly due to the function of depositional environments.•Proper treatment of clay minerals could aid in the prevention of formation damage to a large extent. The Oligocene Barail deltaic sandstones are the main oil reservoirs in Upper Assam Basin. Nonetheless, the diagenetic alterations and their impact on reservoir quality on Barail sandstones are virtually unknown. The present study aims to know the ways diagenesis plays the role for the invariable hydrocarbon production from these clastic reservoirs within the Barail Group. Samples representing the lower unit of Barail Group known as Barail Main Sand (BMS) and the upper unit known as Barail Coal Shale (BCS) were studied using a combination of petrographic, scanning electron microscopy (SEM), X-ray diffraction (XRD) of clay and wireline log techniques. The average framework composition of BMS is Q49.42F4.18R14.75 while the BCS are composed of Q51.33 F3.89 R14.04. The BMS are moderately hard, fine to medium grained, sub angular to sub rounded, moderately well sorted, dominantly of lithic arenite type and porosity value ranges from 10 to 22.01%. The sandstones of BCS Unit are moderately hard, light grey, fine to very fine grained and usually have low porosity except the channel sands. Both the BMS and BCS have undergone various diagenetic alterations which are observed as mechanical compaction, authigenesis of cements and clays, dissolution and alteration of unstable clastic grains. The identified clay minerals are kaolinite, illite and chlorite. Smectite is occasionally observed as mixed layered smectite-illite clay. The diagenetic alterations along with the clay minerals occupying as pore-filling and lining cements have critically influenced the reservoir quality of both BMS and BCS units of Barail Group. Proper treatment of these clay minerals could aid in the prevention of formation damage to a large extent.